The Components of Flemingia macrophylla Attenuate Amyloid β-Protein Accumulation by Regulating Amyloid β-Protein Metabolic Pathway. (7th June 2012) - Lin, Yun-Lian; Tsay, Huey-Jen; Liao, Yung-Feng; Wu, Mine-Fong; Wang, Chuen-Neu; Shiao, Young-Ji
Abstract : Flemingia macrophylla (Leguminosae) is a popular traditional remedy used in Taiwan as anti-inflammatory, promoting blood circulation and antidiabetes agent. Recent study also suggested its neuroprotective activity against Alzheimer's disease. Therefore, the effects of F. macrophylla on A β production and degradation were studied. The effect of F. macrophylla on A β metabolism was detected using the cultured mouse neuroblastoma cells N2a transfected with human Swedish mutant APP (swAPP-N2a cells). The effects on A β degradation were evaluated on a cell-free system. An ELISA assay was applied to detect the level of A β 1-40 and A β 1-42. Western blots assay was employed to measure the levels of soluble amyloid precursor protein and insulin degrading enzyme (IDE). Three fractions of F. macrophylla modified A β accumulation by both inhibiting β -secretase and activating IDE. Three flavonoids modified A β accumulation by activating IDE. The activated IDE pool by the flavonoids was distinctly regulated by bacitracin (an IDE inhibitor). Furthermore, flavonoid 94-18-13 also modulates A β accumulation by enhancing IDE expression. In conclusion, the components of F. macrophylla possess the potential for developing new therapeutic drugs for Alzheimer's disease.